ACTIVITY BASED COSTING DAN SUPPLY CHAIN MANAGEMENT TERHADAP KEUNGGULAN BERSAING - Rima Sundari; Yanisa Zahra (JRAK, 2020)
Indonesia’s agribusiness industry is lagging behind other countries. The factors that influence this are the inaccessibility of the price of agribusiness products and the inefficient logistics activities that occur in the supply chain. Based on these problems, researchers are interested in examining how activity-based costs and supply chain management influence the competitive advantage of PT Perkebunan Nusantara VIII. This study uses the formulation of an associative problem in the form of a causal relationship with the use of a questionnaire. The population and research sample are employees who are in the management line. The analysis technique used are correlation, multiple regression, and determination coefficient analysis. The results showed a significant influence between activity-based costs and supply chain management on competitive advantage at PT. Perkebunan Nusantara VIII either simultaneously or partially.